2020
DOI: 10.52005/belaindika.v2i2.41
|View full text |Cite
|
Sign up to set email alerts
|

Integrasi Pendidikan Lingkungan melalui Pendekatan Ecopedagogy dalam Pembelajaran IPS di Sekolah Dasar

Abstract: Penelitian ini didasarkan atas pentingnya penanaman sikap dalam pembelajaran IPS di sekolah dasar yang menjadi salah satu tujuan IPS yaitu mengembangkan sikap siswa melalui proses pembelajaran. Penelitian difokuskan pada pengamatan mengenai sikap peduli lingkungan siswa sekolah dasar dalam pembelajaran IPS dengan pendekatan ecopedagogy. Tujuan dari penelitian ini adalah untuk mengetahui sejauh mana implikasi pembelajaran terhadap pembentukan pendidikan karakter yang salah satu aspeknya yaitu sikap peduli lingk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Ratnawulan (2014) explained that evaluation techniques must be selected according to the objectives to be achieved and whether evaluation techniques must be considered is the most effective method for determining what students want to know. Aulia et al (2020) and Zubaidillah (2018), explain that evaluation can be identified as a systematic process in determining the extent to which instructional objectives are achieved by students. This opinion is reaffirmed by the notion of evaluation from Muis (2013), namely, in general, evaluation in the implementation of learning is understood as an effort to collect information about the implementation of learning as a basis for making various decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Ratnawulan (2014) explained that evaluation techniques must be selected according to the objectives to be achieved and whether evaluation techniques must be considered is the most effective method for determining what students want to know. Aulia et al (2020) and Zubaidillah (2018), explain that evaluation can be identified as a systematic process in determining the extent to which instructional objectives are achieved by students. This opinion is reaffirmed by the notion of evaluation from Muis (2013), namely, in general, evaluation in the implementation of learning is understood as an effort to collect information about the implementation of learning as a basis for making various decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Ecopedagogy is supported by critical theory and critical pedagogy, in which it is oriented to fraternity and solidarity with the community of life, and in line with the application of Education for Sustainable Development (ESD) principle (Adela & Permana, 2020;Jenkins, 2021;Supriatna et al, 2018). Teachers have to implement ecopedagogy approach in teachinglearning where strategy combinations of dialogue, participative, case study, field study, group discussion, role-play, brainstorming, critical reflection, contextualization, documentation, creative writing, debate, and seminars (based on application and suitability) can be integrated to enhance proenvironmental behaviour case have a look at, subject examine, institution discussion, role-play, brainstorming, crucial reflection, contextualization, documentation, innovative writing, debate, and seminars (based totally on software and suitability) can be integrated to beautify pro-environmental behaviour between students and teachers (Keeley & Benton-Short, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Teachers have a role in providing knowledge to students. The teacher manages the environment as well as possible so that the environment as an essential teaching component is adequately positioned and meets the requirements [9,11]. To create environmental sustainability, teachers must understand the sciences about the environment well.…”
Section: Introductionmentioning
confidence: 99%